2017
DOI: 10.7205/milmed-d-16-00299
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety in Greek Male Veterans After Retirement

Abstract: The sense of satisfaction derived from fulfilling work-related expectations when finishing a career, with changes in everyday life, and smoking and alcohol reduction, may contribute to a better adjustment during the retirement period. To our knowledge, this was the first study examining depression and anxiety levels in Greek veterans, and the sample size was large, covering a randomly chosen veteran population. On the other, it was a convenient sample, although the study results could not focus on direct-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Additionally, overweightness and obesity were found to be negatively related to mental health but positively related with symptoms of sleep disturbances [22] that may indirectly affect stress levels. Further, these findings are in agreement with other studies on veterans [17,23,24]. In this context, a study concerning the associations of anxiety and depression with BMI conducted among 177047 adults in US revealed that obese and overweight people were significantly more likely to be diagnosed with anxiety during their lifetimes [25].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, overweightness and obesity were found to be negatively related to mental health but positively related with symptoms of sleep disturbances [22] that may indirectly affect stress levels. Further, these findings are in agreement with other studies on veterans [17,23,24]. In this context, a study concerning the associations of anxiety and depression with BMI conducted among 177047 adults in US revealed that obese and overweight people were significantly more likely to be diagnosed with anxiety during their lifetimes [25].…”
Section: Discussionsupporting
confidence: 91%
“…The current study explored the impact of socio-demographic features and issues concerning the retirement procedures and life after retirement on anxiety and depression levels among navy veterans after retirement. Our findings concerning depression (severe: 6.5%, moderate and mild: 30%) are comparable to those of a previous study conducted among 502 Greek military veterans that revealed 3.8% had severe depression, and 23.2% had depression symptoms that ranged from mild to moderate [17].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Taking into consideration that the majority are current veteran retirees [103] also suffering from other comorbidities [11], medication for chronic conditions such as COPD has become inaccessible for many patients [11,13,86,103]. The mean annual cost of treatment for each stable COPD patient has been estimated to be €952.92, of which €239.91 has been paid by the patients [13].…”
Section: Treatment Adherence During Crisismentioning
confidence: 99%
“…It is also worth noting that the high level of CG at the beginning of the line (other professional jobs) suggested that employment in previous life was a potential risk factor for CG. The result is reasonable as Kypraiou et al () stated that people with a professional occupation before retirement would experience a larger life transition, which might lead to greater dissatisfaction in their life after retirement. Such a life transition might lower their preparedness and ability to adapt following the death of their spouse.…”
Section: Discussionmentioning
confidence: 56%